Implementasi Algoritma String Matching Boyer Moore Untuk Pencarian Nama Dokumen Pada Rancang Bangun Sistem Pengarsipan Dokumen (Studi Kasus: Sistem Pengarsipan Dokumen Satuan Polisi Pamong Praja Kabupaten Bantul) - Shulhi Fifuadi; Deden Hardan Gutama; Andri Pramuntadi; Dhina Puspasari Wijaya (Majalah Ilmiah UNIKOM, 2024)
The Civil Service Police Unit (Satpol PP) is a regional apparatus or institution tasked with assisting the Governor or Regent in carrying out regional government affairs. In the field sector, the Bantul Regency Satpol PP has a Secretariat sector. One of the functions of the secretariat at the Bantul Regency Satpol PP is as a place for archiving or storing documents within the Satpol PP environment. This secretariat sector still uses manual methods to search for archival document data that will be needed again. From interviews obtained at the Bantul Regency Satpol PP, they do not yet have a system or application for storing archival documents. Then a manual search is carried out by sorting the documents one by one in a filling box or filing cabinet which contains many documents from year to year. This is less effective. From the findings of these problems, a solution emerged to create a website-based archiving system that can simplify the work of Satpol PP secretariat members and as a digital document storage that can simplify document archiving and searching by applying Boyer Moore's String Matching algorithm in searching data. The Boyer Moore algorithm is an algorithm for searching for a keyword (pattern) in text by comparing characters or letters from the right of the pattern to the left. The test results were carried out by comparing the search speed of the Boyer Moore algorithm and without the algorithm. The search was carried out for 40 document data and resulted in an average time of 0.000107 seconds for searching using the Boyer Moore algorithm. Key Words: Boyer Moore String Matching Algorithm, Pattern, Filling Box, Filling Cabinet, Website.